Activating Nitrogen‐doped Graphene Oxygen Reduction Electrocatalysts in Acidic Electrolytes using Hydrophobic Cavities and Proton‐conductive Particles. Issue 51 (17th November 2022) - Singh, Santosh K.; Takeyasu, Kotaro; Homma, Kaito; Ito, Shigeharu; Morinaga, Takashi; Endo, Yuto; Furukawa, Moeko; Mori, Toshiyuki; Ogasawara, Hirohito; Nakamura, Junji
Abstract: Although pyridinic‐nitrogen (pyri‐N) doped graphene is highly active for the oxygen reduction reaction (ORR) of fuel cells in alkaline media, the activity critically decreases under acidic conditions. We report on how to prevent the deactivation based on the mechanistic understanding that O 2 + p y r i - N H + + e - → O 2, a + p y r i - N H O_2+pyri -NH^++e^-→ _ ^ O_2, a+pyri -NH governs the ORR kinetics. First, we considered that the deactivation is due to the hydration of pyri‐NH +, leading to a lower shift of the redox potential. Introducing the hydrophobic cavity prevented the hydration of pyri‐NH + but inhibited the proton transport. We then increased proton conductivity in the hydrophobic cavity by introducing SiO2 particles coated with ionic liquid polymer/Nafion® which kept the high onset potentials with an increased current density even in acidic media. Abstract : We report on how to overcome the deactivation of N‐doped graphene catalysts for oxygen reduction reaction in acidic media based on the mechanistic understanding. Compatible suppression of the hydration of protonated pyridinic‐N (pyri‐NH + ) by hydrophobic cavity and the introduction of proton conductivity by proton‐conductive particles made the activity of N‐doped graphenes close to that of Pt catalysts under acidic conditions.